For whom should we gamify? Insights on the users intentions and context towards gamification in education - Toda, Armando; Pereira, Filipe Dwan; Klock, Ana Carolina Tomé; Rodrigues, Luiz; Palomino, Paula; Oliveira, Wilk; Oliveira, Elaine Harada Teixeira; Gasparini, Isabela; Cristea, Alexandra Ioana; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
Gamification design in educational environments is not trivial and many variables need to be considered to achieve positive outcomes. Often, educators and designers do not know when the students intentions on the use of gamified environments might influence their experience. Based on this premise, this paper describes an exploratory study on the users intention to use gamification, focusing on its influence in the field of education. We conducted a survey study with participants (N=1.692) and analysed their answers using unsupervised data mining techniques. As a result, we obtained empirical evidence showing that demographic and contextual variables influence (positively and negatively) peoples intention to use gamification. This evidence can support designers and educators better understand whether and when they should or should not gamify a learning environment.